1995
DOI: 10.1037/0021-9010.80.6.685
|View full text |Cite
|
Sign up to set email alerts
|

Team performance on monitoring tasks: An examination of decision errors in contexts requiring sustained attention.

Abstract: for providing helpful comments on a previous version of this article. We also thank Anders Johanson, who developed the TIDE 2 software used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…In error situations, individuals not only have to deal with the task at hand but also with the error and its potential consequences, along with their negative self-image. In organizations in which errors tend not to be punished and are accepted as part of work, the additional cognitive demands of errors may be potentially reduced because there is less need for individuals to cope with their negative self-image by hiding errors or blaming others (Hockey, 1996; see also Hollenbeck, Ilgen, Tuttle, & Sego, 1995). Moreover, because strain may lead to additional errors, it is likely that in organizations with low-error aversion culture, secondary errors tend to be avoided, and error handling is done more effectively, ultimately resulting in better firm performance.…”
Section: Error Management Culturementioning
confidence: 99%
“…In error situations, individuals not only have to deal with the task at hand but also with the error and its potential consequences, along with their negative self-image. In organizations in which errors tend not to be punished and are accepted as part of work, the additional cognitive demands of errors may be potentially reduced because there is less need for individuals to cope with their negative self-image by hiding errors or blaming others (Hockey, 1996; see also Hollenbeck, Ilgen, Tuttle, & Sego, 1995). Moreover, because strain may lead to additional errors, it is likely that in organizations with low-error aversion culture, secondary errors tend to be avoided, and error handling is done more effectively, ultimately resulting in better firm performance.…”
Section: Error Management Culturementioning
confidence: 99%
“…In CORP, the organization faces a sequence of radar-detection problems, as documented in other studies (Hollenbeck et al 1995) and reflected in real-world cases (Roberts and Dotterway 1995). Each problem is defined as a single aircraft moving through the airspace.…”
Section: Method: a Matched Analysismentioning
confidence: 99%
“…An example may be the incident, which is described below, of an Iran Air flight being shot down by the USS Vincennes (Rochlin 1991). We believe that there may be a systematic approach to exploring organizational performance during crises through observable factors including expertise, organizational design, and task environment , Hollenbeck et al 1995, Levinthal and Warglien 1999, Pearson and Mitroff 1993.…”
mentioning
confidence: 99%
“…Crew resource management addresses fatigue as one of the factors of which crews should be made aware and trained to expect and control (Helmreich, Merritt, & Wilhelm, 1999); however, the specific effects of fatigue due to sleep loss upon team performance do not seem to be provided by this literature. (Hollenbeck, Ilgen, Tuttle, & Sego, 1995) performed research on sustained attention in a team environment using well-rested volunteers. These researchers found that decrements on vigilance tasks at the team level were similar to those at the individual level.…”
Section: Introductionmentioning
confidence: 99%